Peningkatan pertumbuhan benih ikan tengadak, Barbonymus schwanenfeldii (Bleeker 1853) melalui pengaturan salinitas dan kalsium - Dini Islama; Kukuh Nirmala; Ani Widiyati (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2014)
This study aimed to determine the optimal salinity and calcium levels in rearing media to increase the growth of tinfoil barb seed (Barbonymus schwanenfeldii). The experiment design was arranged in factorial completely randomized design with three replications. The treatment included three media salinity levels, that is, 0 ppt, 3 ppt, 6 ppt and four addition calcium, that is, 0 mg L